Establishing the feasibility of exercise breaks during university lectures - Hayes, Scott M. (Frontiers in Sports and Active Living, 2024)
It is important that principles of laboratory-based studies with implications for academic performance be implemented in naturalistic learning environments to gauge their feasibility. Here, an adaptation of a laboratory-based study of exercise breaks during a single video lecture was implemented during large, in-person lectures at Ohio State University for the duration of a semester. The rationale for this approach was based on findings that research participants who took exercise breaks during a video lecture were more likely to be on task towards the end of the lecture and performed significantly better on a multiple choice exam. The current project had three goals: (1) Establish the feasibility of integrating student-led exercise breaks during in-person lectures in a large university setting (2) Provide practical guidelines for implementing exercise breaks during in-person lectures (3) Provide preliminary evidence of positive effects of exercise breaks in a higher-education setting. One to two student-led exercise breaks (5 min each) were implemented during each 80 min, in-person lecture for the duration of a semester in four upper level Psychology courses with student enrollment ranging from 20 to 93 students (total enrollment = 223 students). Students reported that the exercise breaks were a strength of the courses and a positive experience, including self-reported improvement in attention to lecture content. Self-reported quantitative data indicated that exercise breaks improved attention, increased course enjoyment, and enhanced peer engagement. Compared to other classes, the students preferred exercise breaks during lectures. The current approach establishes the feasibility of integrating exercise breaks in a large, in-person university lecture environment for the duration of a semester with preliminary data indicating a positive impact on attention, engagement, and enjoyment. Practical guidelines for implementing exercise breaks during in-person lectures are provided.